2021
DOI: 10.2478/sjph-2021-0017
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ knowledge of patient safety and development of competences over their academic years: Findings from a longitudinal study

Abstract: Introduction Future nurses should possess the knowledge and competences necessary to ensure patient safety. However, little evidence is available on the way in which students learn patient safety-related principles over time. This study explored the progress of a cohort of Italian undergraduate nursing students as they acquired patient safety knowledge and competences from time of enrolment to graduation. Methods A longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…One reason for this could be the increased time available to second-year students compared with fourth-year students to prepare for the assessment of the module. An interesting approach to evaluating differences in knowledge between different year groups has been taken by Bressan et al 28 They followed the same student groups each year, their performance were measured at the end of year 1, 2, and 3, and they found that the knowledge on PS issues remained stable. Fourth-year students had significantly higher pretest scores in the STS component in contrast to second-year students.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this could be the increased time available to second-year students compared with fourth-year students to prepare for the assessment of the module. An interesting approach to evaluating differences in knowledge between different year groups has been taken by Bressan et al 28 They followed the same student groups each year, their performance were measured at the end of year 1, 2, and 3, and they found that the knowledge on PS issues remained stable. Fourth-year students had significantly higher pretest scores in the STS component in contrast to second-year students.…”
Section: Discussionmentioning
confidence: 99%
“…They should have the knowledge necessary to ensure patient safety. However, there needs to be more evidence on how students learn patient safety principles during their studies (Bressan et al, 2021). Therefore, our study aimed to collate existing empirical research studies on factors affecting the perception of patient safety from the perspective of nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…3 The results of this study are in line with the results of Lee, 16 where the scores for the skills and knowledge of the study participants were lower than the scores for attitudes. 16 Meanwhile, the results of the study by Bressan V. et al 4 showed that student knowledge remained stable, while nursing student competency in patient safety issues increased over time. Students are more vulnerable at the end of the first year, when they seem overly confident about patient safety issues.…”
Section: Discussionmentioning
confidence: 99%
“…Nurse graduates must have sufficient knowledge and soft skills to identify potential safety risks and must have the confidence to protect patients from preventable harm because they are future health care professionals. 2,4 The self-confidence and skills of graduates are closely related to the safety practices received while participating in the educational process at tertiary institution. 5 Therefore, universities as providers of vocational education are responsible for developing student abilities and preparing future nursing workers to practice according to patient safety standards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation